[First floor stairwell and atrium construction of Kennedy Library] - P. K. Phillips::::::photographer::: (1978)
The first floor stairwell and atrium of Kennedy Library, before the construction of a separating wall. The first four floors have been completed. Construction materials and equipment are pictured.